The Biological alternative to the management of the spot grain complex in rice crops in Babahoyo, province of Los Ríos, Ecuador. (Revista Científica Ciencias Naturales y Ambientales, 2017)
I studied ways to control complex called as spot grain rice farming and its effect on grain yield. In this study incidence of fungi that attack the grain he was found. Under field conditions are extremely variable from damage and forms of manifestation. However in this work it was consolidated on information collected in the application of alternative control and managementof these pathogens. The objective of this work was to evaluate the use of ecological alternatives for spot management to identify the antagonistic effect of biocontrollers in the international context and to compare the effectiveness of chemical products against biological alternatives (bioproducts). Control with agrochemicals is the most widely used alternative to the application of biological type, which affect the ability of inoculum of infection. The use of these alternatives are still being examined, the experimental results are still vague and in some few cases for specific interactions. Positive responses were reported in early applications with biological alternatives, the most common use of antagonistic as Bacillus and Trichoderma, which inhibit the formation of the causal agents stained in rice cultivation.
Keywords: Alternatives; stained; pathogens; control; fungicidas